Lipid profiles and their relation to glycemic control in Saudi Arabia: The role of altitudes and environmental factor - Saif Aboud M. Alqahtani (Journal of Family Medicine and Primary Care)
Background: The height from sea levels, environmental factors, human–environment interactions, and lifestyle significantly influence the lipid profile and glycemic control of a population. Objective: This study aims to explore the influence of altitude on lipid profiles and glycemic control among the Saudi population at sea level and high altitude. Methods: In this retrospective cross-sectional study, a large dataset of patients of both gender and over 30 years old attending internal medicine clinics from two different regions at different heights from sea level, Jeddah (sea level) and Asir region (high altitudes) and referred to commercial laboratories for glycated haemoglobin (HbA1c) and lipids profile. Results: Compared to the Asir region, the Jeddah region had significantly higher mean values for fasting blood sugar (FBG), total cholesterol (TC), low-density lipoprotein (LDL-C), and triglycerides (TG) (P < 0.05). Every 1 mg/dL increase in FBG results in a 0.662 mg/dL increase in TG from the Jeddah region. However, it was a 0.318 mg/dL increase in TG from the Asir region. HbA1c demonstrated a significant (P < 0.05) strong positive correlation with TC, low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), and lipid ratio. FBG levels were also associated with a high level of TC/HDL-C (β = 0.137 95% confidence interval [CI]: 0.11–0.21; P < 0.05), LDL-C/high-density lipoprotein cholesterol (HDL-C) (β = 0.50; 95% CI: 0.31–1.49; P < 0.05), and TG/HDL-C (β = 0.14; 95% CI = 0.12–0.15; P < 0.05) in Jeddah region. However, significantly high blood pressure was observed in the population from high altitudes. Conclusion: Our results demonstrated a significant positive correlation between lipid profile and glycemic control with high prevalence at sea level.